DEVELOPMENT OF GEOTHERMAL ENERGY UTILIZATION HARDWARE BASED ON THERMOELECTRICITY - Marpaung, Harapan
Indonesia has the second-largest geothermal potential in the world. Most geothermal power plants still use high and medium temperatures because they are more economical. The utilization of low-temperature geothermal potential is still limited to power plants using binary cycle or direct-use methods and is still rare in Indonesia. Ciater hot springs are part of the northern geothermal manifestation zone of Mt. Tangkuban Parahu. The temperatures of Ciater Hot Springs are 40,8°C and 42,8°C, so they are categorized as low-temperature geothermal potential and have been used for tourism purposes, namely Sari Ater Hot Spring. The availability of low-temperature heat sources from these hot springs can be used for power generation. Semiconductor thermoelectric generator (TEG), which works based on the temperature difference between the two sides, is an alternative power generation technology. With the various advantages of TEG over other devices, a TEG-based power generation (PLBT) will be developed that has a compact size, is portable, and can operate on heat sources in both steam and liquid phases. The issue of the low efficiency of the TEG is compensated for when the PLBT is applied to the freely available Ciater hot spring. PLBT hardware is designed and manufactured in stages and undergoes a series of tests using data acquisition tools to ensure the performance of each component. Tests on five types of TEG elements in mini-scale plants show that the TEG element type TEG1-241-1.4-1.2 produces the largest output power of 4,90 W at a temperature difference of ?T = 100 °C and operates stably. Tests on ready-touse aluminum radiators also performed well based on their heat transfer parameters. A set of 2 TEG elements flanked by hot-side and cold-side radiators packaged in a module called M2T. After obtaining a well-performing M2T module through tests on medium-scale plants, the M8T module that houses 8 TEG elements was developed and tested. The radiators on the M8T are 25 cm × 12,5 cm × 1,4 cm, placed flanking 8 TEG elements in 2 lanes and added thermal grease to improve heat transfer. The PLBT comprises two frame blocks with 7 M8T modules as the main components. Each block is 40 cm x 28 cm x 50 cm, and each block weighs about 20 kg. This TEG design offers a compact size and is portable, with a total number of 56 TEG elements. The PLBT also features flexible wiring between TEG elements and between M8T modules. Each M8T module is connected to hoses for hot fluid (water or steam) and cold water distribution. The simulation of hot steam in the M2T and M8T modules tests was performed using a previously tested steam boiler. Laboratory-scale PLBT testing using a steam boiler heat source produces power up to 16,27 W at ?T 60°C for each M8T module. While the test using a hot water heat source produces a maximum power of 4,60W at ?T 45°C. These results show that this PLBT hardware can work well with steam and hot water heat sources. The PLBT field test was conducted at the Ciater Hot Spring at the Sari Ater Hot Spring tourist attraction in Ciater Village, Ciater District, Subang Regency, West Java Province. The PLBT hardware is connected through a hose to the hot water source from the bathtub and the cold water circulation from the faucet in the garden. The PLBT test results at Ciater Hot Springs produced 9,80 W at ?T 17,5 °C and could light several LED lamps. PLBT hardware can operate normally and stably in low-temperature geothermal, i.e., hot springs.